The involvement of hydrographic surveyor in the installation of offshore oil platfrom [compact disc] - 381084 Rajendran Superamaniam (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik) - Universiti Teknologi Malaysia, 2008